Prevalence of chronic kidney disease in the elderly using the ASPirin in Reducing Events in the Elderly study cohort. Issue 12 (7th May 2019) - Polkinghorne, Kevan R; Wolfe, Rory; Jachno, Kim M; Wetmore, James B; Woods, Robyn L; McNeil, John J; Nelson, Mark R; Reid, Christopher M; Murray, Anne M; ,
ABSTRACT: Aim: The prevalence of chronic kidney disease (CKD) in the elderly is controversial because age‐related decline in kidney function may not truly reflect underlying kidney disease. We estimate the baseline prevalence and predictors of CKD using the CKD Epidemiology Collaboration (CKD‐EPIeGFR ) and Berlin Initiative Study 1 (BIS1eGFR ) eGFR equations in the ASPirin in Reducing Events in the Elderly (ASPREE) trial cohort of healthy older participants. Methods: GFR was estimated using CKD‐EPI and BIS1 equations. CKD was defined as eGFR <60 mL/min/1.73 m 2 or ≥ 60 mL/min/1.73 m 2 with urine albumin creatinine ratio (UACR) ≥ 3 mg/mmol. Logistic regression was used to identify predictors of CKD prevalence defined by each eGFR equation. Results: Data for analysis were complete for 17, 762 participants. Mean age was 75.1 years (SD 5); 56.4% were female, 76.4% had hypertension, 9% had diabetes mellitus. Mean CKD‐EPIeGFR was 73.0 (SD 14.2), compared with mean BIS1eGFR of 62.7 (11.4). Median UACR was 0.8 (IQR 0.5, 1.5) mg/mmol. Prevalence of CKD by CKD‐EPIeGFR was 27% (predominantly due to normoalbuminuric stage 3a CKD), substantially lower than 47.1% by BIS1eGFR ; the difference was predominantly driven by reclassification of individuals from G1 and G2 CKD to stage G3a without albuminuria. Increased prevalence of CKD by either equation was related to older age, hypertension, diabetes, or higher body mass index. Conclusions: Prevalence of CKD with CKD‐EPIeGFR was 27%, and doubled using the elderly specific BIS1eGFR, with most participants reclassified from stage 2 to stage 3a. Increased prevalence of CKD was related older age, hypertension, diabetes, or increased body mass index. SUMMARY AT A GLANCE: Chronic kidney disease (CKD) is common and increases with age even in healthy elderly people. The elderly specific Berlin Initiative Study 1 (BIS1eGFR) estimated glomerular filtration rate (eGFR) equation BIS1eGFR substantially increases CKD prevalence, largely by reclassifying elderly participants from G1 and G2 CKD to stage G3a without albuminuria to stage 3a CKD.